Review Peran suplemen probiotik dan herbal sebagai Antimikrobial, Antioksidan, and Imunomodulator terhadap Aeromonas hydrophila : Review artikel suplemen herbal dan probiotik untuk melawan Aeromonas hydrophila - Dahliatul Qosimah; Laminem; Candra Mandasari; Dyah Setyawati (Postgraduate, University of Mataram, 2023)
Aeromonas hydrophila (A. hydrophila) are classified as zoonotic and opportunistic bacteria. Natural immunostimulants such as herbs are biodegradable and safe for the environment and host health. There has been no systematic review of using these natural ingredients to treat or prevent A. hydrophila infection. This review aims to demonstrate the role of herbs and probiotics as antibacterial, antioxidant, and immunostimulatory against A. hydrophila infection. This study deployed systematic and comprehensive literature from PubMed, Google Scholar, and Scopus from 2012 to 2022, with keywords: A. hydrophila, herbal, probiotics, antioxidant, immunomodulator, antibacterial. Data are obtained from journals, proceeding of research results, excluding article reviews. The review results indicate that the utilization of these two ingredients (herbs and probiotics) is potential to prevent A. hydrophila infection in animal models with variation action mechanisms and dose administration. However, an inappropriate combination of herbs and probiotics leads to the development of resistance and toxicity profile, thereby requiring further research to standardize such combination prior to application for humans or animals.